Pemberdayaan Womenpreneur Melalui Optimalisasi Pemanfaatan Hasil Olahan Hutan Dan Strategi Pemasaran Digital Pada Darma Iikp Perhutani Bandung - Kadarisman Kadarisman; Yati Yati; Fitra Jaya; Gayatria Oktalina; Agnisa Widayanti (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service activity aims to strengthen the economic capacity of members of Darma IIKP Perhutani Bandung through a womenpreneur empowerment program based on forest product processing and digital marketing. Women in the Perhutani work environment have significant entrepreneurial potential, yet face constraints including limited product innovation and restricted market access. A participatory approach was employed, encompassing outreach, technical production training, digital literacy training, and mentoring evaluation. Results indicate an 80% improvement in participants' technical ability to manage and upload product content to social media following one-on-one mentoring sessions. Participants also demonstrated enhanced understanding in diversifying forest-based processed products such as premium forest honey, forest coffee, essential oils, and eco-print crafts. This program is expected to foster sustainable household economic independence within the Perhutani Bandung community